Emotional Intelligence Among Adolescents: A Psychological Insight Into Developmental Dynamics And Predictive Factors - Srinivas Rao, Bhuma; A.G, George.; Dubisetty, Mallikarjuna Rao; Choudhari, Dashrath; Kodicherla, Manish; Lingala, Jagruth (Journal of Neonatal Surgery, 2025)
Emotional Intelligence (EI) is a crucial component of adolescent development, significantly influencing their academic success, mental health, interpersonal relationships, and overall psychological well-being. Adolescents face a unique combination of biological, cognitive, and social changes, making emotional regulation and understanding essential during this formative period. This study aims to assess the level of emotional intelligence among adolescents and examine how it varies across gender, the extent of parental involvement, and academic performance. A sample of 200 school-going adolescents (100 males and 100 females), aged between 13 and 18 years, was selected using purposive sampling from two states in India: Telangana and Chhattisgarh. Standardized tools were employed, including the Emotional Intelligence Scale (EIS), Parental Involvement Rating Scale, and academic records. The data were analyzed using descriptive statistical methods, independent t-tests, Pearson's correlation, ANOVA, regression analysis, and Tukey's HSD post-hoc comparisons. Results of the study indicated that women scored significantly higher than males when it came to emotional intelligence, particularly in the areas of empathy and emotional regulation. A significant and robust positive association was observed between emotional intelligence and the level of parental involvement, while academic performance also showed a moderate positive association. Regression analysis revealed that parental involvement was the most significant predictor of EI, followed by academic performance. ANOVA results indicated significant differences in EI across varying levels of parental involvement, with post-hoc analysis confirming that adolescents with high parental support demonstrated notably higher EI. The findings underscore the importance of supportive parenting practices and structured school interventions aimed at enhancing emotional competence. Educational policies should integrate emotional intelligence training into school curricula and parenting programs to promote healthy adolescent development. The study adds to the growing body of psychological research advocating for socio-emotional learning (SEL) as a core educational objective.